Pengaruh Kualitas Layanan Pegawai Terhadap Kepuasan Nabasah Pada Koperasi Binawarga Salobulo Kabupaten Wajo - Andi Yuniarti; Jumardi Awal; Akbar (Precise Journal of Economic, 2025)
This study aims to analyze the effect of employee service quality on customer satisfaction at the Binawarga Salobulo Cooperative, Wajo Regency. The background of this study is based on the importance of service quality as a major factor in creating and maintaining customer satisfaction and loyalty amidst increasingly fierce competition among financial institutions. This study uses a quantitative approach with a causal associative design. The population in this study amounted to 220 active customers with a sample of 69 respondents selected using a purposive sampling technique. The results show that employee service quality has a positive effect on customer satisfaction, with a regression coefficient value of 1.428, meaning that every increase in service quality will increase customer satisfaction by 1.428 units. The correlation coefficient value of 0.639 indicates a strong and positive relationship between the two variables, while the determination coefficient value of 0.411 explains that 41.1% of the variation in customer satisfaction can be explained by employee service quality. These findings confirm that the better the quality of service provided, including timeliness, courtesy, comfort, and completeness of service, the higher the level of customer satisfaction at the Binawarga Salobulo Cooperative, Wajo Regency